Thermo-Mechanical Behavior and Hydrolytic Degradation of Linear Low Density Polyethylene/Poly(3-hydroxybutyrate) Blends - Rigotti, Daniele; Dorigato, Andrea; Pegoretti, Alessandro (Frontiers in Materials, 2020)
In this work, a commercial linear low density polyethylene (LLDPE) utilized for packaging applications was melt compounded with different amounts (from 10 wt% up to 50 wt%) of poly(3-hydroxybutyrate) (P(3HB)), with the aim to evaluate the possibility to partially replace LLDPE with a biodegradable matrix obtained from renewable resources. The processability, microstructural and thermo-mechanical behaviour of the resulting blends was investigated. Melt flow index (MFI) values of the LLDPE matrix were not much affected until a P(3HB) content of 20 wt%, while for higher P(3HB) concentrations an evident decrease of the viscosity was detected. Scanning electron microscope (SEM) observations on the blends highlighted that at limited P(3HB) concentrations the secondary phase was homogeneously dispersed in form of isolated domains, while at a P(3HB) content of 50 wt% a continuous layered morphology could be detected. Thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FT-IR) did not evidence any chemical or physical interaction between the two polymer phases. Quasi-static tensile tests and dynamical mechanical analysis showed that the introduction of P(3HB) led to a pronounced stiffening effect, while the progressive drop of the yield and ultimate mechanical properties could be attributed to the weak interfacial adhesion and poor compatibility between the two matrices. The resistance to hydrolytic degradation of the LLDPE/P(3HB) blends was evaluated over a period of 100 days of immersion in water at 50 °C. It was observed that the weight variation and the decrease of the tensile properties due to the hydrolytic process on the biodegradable phase were evident only for a P3HB content of 50 wt%. In conclusion, this work showed that the partial replacement of LLDPE with a biobased P(3HB) could lead to the development of an innovative blend with good processability and mechanical properties, until a P(3HB) amount of 20 wt%.